Cellular T-cell immune response profiling by tetravalent dengue subunit vaccine (DSV4) candidate in mice - Aggarwal, Charu; Ramasamy, Viswanathan; Garg, Amit; Shukla, Rahul; Khanna, Navin (Frontiers in Immunology, 2023)
While most vaccines aim to develop a solid humoral and neutralizing antibody response against the pathogen, an effective vaccine candidate should be able to stimulate both the B-cell mediated humoral immunity, and T-cell mediated cellular immunity. The focus of vaccinology is rapidly gaining to generate T cell responses, which can mediate pathogen clearance and help B cells leading to protective antibody responses. Here we evaluate the cellular immune response of the pre-clinical tetravalent dengue subunit vaccine candidate, DSV4, in mice. While we have shown previously that DSV4 induces type-specific neutralizing antibody responses in mice, in this study, we show that the vaccine candidate DSV4 well induces dengue-specific T- cell responses evaluated by their ability to produce IFN-γ. In addition to IFN-γ secretion by both CD4+ and CD8+ T-cells in immunized mice, we observed that DSV4 also induces a higher frequency and cytokine functions of follicular CD4+ helper T-cells (TFH). These cytokines lead to an efficient germinal centre reaction and potent B cell antibody response. Apart from TFH response, DSV4 stimulated Type 1 T helper cells (TH1) which is characteristic of a viral infection leading to secretion of pro-inflammatory cytokines and phagocyte-dependent protective immune responses. Our study highlights that DSV4 can mediate both arms of adaptive immunity-humoral and cell-mediated immunity in mice. By elucidating vaccine-specific T cell response, our work has implications in showing DSV4 as an effective, type-specific and safe dengue vaccine candidate.